Fenomenul standardului jazzistic în repertoriul formaţiei „UNIVOX VOCAL BAND” - Tcacenco (Arta, 2017)
This article is dedicated to jazz standard phenomenon as a key component of jazz music, an important tool of preserving and developing the jazz tradition. The aim of the author is to study the treatment of jazz standards in the arrangements made and performed by the Moldovan artistic group ”Univox Vocal Band”. The analysis is based on jazz songs of various genres, such as the legendary Christian hymn ”Amazing Grace”, the ”Christmas Song” borrowed from Mel Tormé’s repertoire, the ”Ol' Man River” song from the musical ”Boat Show” composed by J. Kern, as well as a song ”Ain’t No Sunshine” sang by R&B singer Bill Withers. Based on the analysis made, the most representative features of the selected compositions are revealed, all of them reflecting the assimilation of universal traditions of jazz standard interpretation. Thus, at the melodic level we can see the use of the blues patterns, at the harmonic level – the utilization of blue scale, blue chords, barbershop harmonies. At the rhythmic level musicians transmit such specific jazz features, as secondary rag, swing feeling, and on the texture level one can observe the application of specific techniques: walking bass, riffs, call-and-response, ostinato, poliostinato.